If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5log(x + -2) = 10 Reorder the terms: 5glo(-2 + x) = 10 (-2 * 5glo + x * 5glo) = 10 (-10glo + 5glox) = 10 Solving -10glo + 5glox = 10 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -10 + -10glo + 5glox = 10 + -10 Combine like terms: 10 + -10 = 0 -10 + -10glo + 5glox = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-2 + -2glo + glox) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-2 + -2glo + glox)' equal to zero and attempt to solve: Simplifying -2 + -2glo + glox = 0 Solving -2 + -2glo + glox = 0 Move all terms containing g to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -2glo + 2 + glox = 0 + 2 Reorder the terms: -2 + 2 + -2glo + glox = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -2glo + glox = 0 + 2 -2glo + glox = 0 + 2 Combine like terms: 0 + 2 = 2 -2glo + glox = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| y=5x^2+14x+1 | | 4(0)+n=10 | | 2d+4c=11 | | 10q-9q=17 | | (2x-8)-.5(9-4x)+2.5= | | 2(q+6)-4=2 | | 2x^2-5x+82=0 | | 9t+8=10t | | 10h+2h-8h=16 | | -7x+5=-12+4 | | -n^2+16n-34=-4n^2+1 | | 6=9(3+7f) | | -2(q+9)=2 | | 3/8=a/8 | | -5p+17=-18 | | 4(3x-1)=5x+6 | | 4/15-2/3 | | (x/2)-15=125 | | 2z-2x+2y+2z^3=0 | | -.75x+6=-12 | | 1h+7=17 | | v(x)=(12-2x)(16-2x)(x) | | 10k-11k=20 | | 0x+2y+2z=0 | | -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 | | y=2+13y | | 20x+y=180 |